Genetic analysis of a novel invasion of Puerto Rico by an exotic constricting snake (2013)
The tropical island Puerto Rico is potentially vulnerable to invasion by some species of exotic snakes; however, until now no established populations had been reported. Here we report and genetically characterize the nascent invasion of Puerto Rico by an exotic constricting snake of the family Boidae (Boa constrictor) using mtDNA and microsatellite data. Over 150 individual B. constrictor have been removed from Mayagüez municipality since May 2011, and our results from the genetic analysis of 32 individuals suggest that this population was recently founded by individuals of one subspecies from a genetic lineage common to zoo and breeding collections, but that the potential propagule pool consists of two subspecies. We also suggest that anthropogenic long-distance dispersal within the island of Puerto Rico may be occurring from the established population, with implications for further establishment across the island. This study represents the first report of the naturalization of an invasive species of boid snake in Puerto Rico and will be important in determining mitigation strategies for this invasion as well as providing a basis for comparison to other on-going studies of invasive snakes.